DISTRIBUTION PATTERN OF TOTAL SUSPENDED SOLIDS (TSS) IN KAMPAR RIVER ESTUARY, PELALAWAN REGENCY, RIAU PROVINCE - Melas, Febi Betania; Mubarak, Mubarak; Rifardi, Rifardi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
The Kampar River Estuary is the main river in Riau province, which empties into the Malacca Strait and has a unique potential for research. The characteristics of the Kampar River Estuary are concurrent and have high tidal elevations, resulting in the occurrence of a Tidal Bore, which is referred to as Bono. The impact of sedimentation is generally quite detrimental, namely the siltation in several places, such as the waters of the Kampar River Estuary, which are dense areas of human activity. This study aimed to determine the relationship between hydrodynamic patterns, suspended solids' distribution pattern, and the concentration value of suspended solids distribution in the Kampar River estuary. This research method is surveyed and discussed descriptively. Current patterns affect the distribution of sediments in the Kampar River estuary. The TSS distribution pattern tends to follow the same direction as the movement of tidal currents where, during high tide, it tends to lead to the southwest of the Kampar River estuary, while during low tide tends to lead to the northeast and northwest, it this is because, in the Kampar River estuary, there is an island that makes the mouth of the Kampar River estuary V-shaped. Between hydrodynamic patterns and TSS distribution patterns, there is a moderate negative relationship (r = 0.50), which means that there is a significant influence between hydro patterns and TSS distribution patterns in the waters of the Kampar River estuary, between hydrodynamic patterns and TSS distribution patterns in the waters of the Kampar River estuary. The lowest value of TSS concentration in the waters of the Kampar River Estuary at high tide to low tide is Station 7, with a range of 102 mg/L, and the highest value at Stations 3, 4, and 9. At station 3, there are values ranging from 1756 mg/L; at Station 4, there are values ranging from 2823 mg/L; and at Station 9, there are values ranging from 1269 mg/L; the high concentration of TSS results in low brightness in the study area